2016
DOI: 10.1038/srep38766
|View full text |Cite
|
Sign up to set email alerts
|

Potentiation of Amitriptyline Anti-Hyperalgesic-Like Action By Astroglial Connexin 43 Inhibition in Neuropathic Rats

Abstract: Antidepressants, prescribed as first line treatment of neuropathic pain, have a limited efficacy and poorly tolerated side effects. Because recent studies pointed out the implication of astroglial connexins (Cx) in both neuropathic pain and antidepressive treatment, we investigated whether their blockade by mefloquine could modulate the action of the tricyclic antidepressant amitriptyline. Using primary cultures, we found that both mefloquine and amitriptyline inhibited Cx43-containing gap junctions, and that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 65 publications
2
32
0
Order By: Relevance
“…Taking together, we demonstrated here that THN102 enhanced both locomotor activity and glucose metabolism in cortical and subcortical areas involved in the regulation of sleep-wake cycle and behaviors. Our results further support the hypothesis that astrocyte connexins are involved in pharmacological responses of psychoactive drugs such as modafinil ( Duchêne et al, 2016 ; Jeanson et al, 2016 ; Charvériat et al, 2017 ).…”
Section: Discussionsupporting
confidence: 87%
“…Taking together, we demonstrated here that THN102 enhanced both locomotor activity and glucose metabolism in cortical and subcortical areas involved in the regulation of sleep-wake cycle and behaviors. Our results further support the hypothesis that astrocyte connexins are involved in pharmacological responses of psychoactive drugs such as modafinil ( Duchêne et al, 2016 ; Jeanson et al, 2016 ; Charvériat et al, 2017 ).…”
Section: Discussionsupporting
confidence: 87%
“…These findings are consistent with in vitro studies reporting a positive impact of antidepressant drugs of gap junction activity in rat primary cultures of cortical astrocytes and in human astrocytoma cell lines . Regarding hemichannels, a recent in vitro study has reported an unambiguous inhibitory action of SSRIs but also of Norepinephrine Reuptake Inhibitors and Serotonin‐Norepinephrine Reuptake Inhibitors on their functional activity with different degrees of efficacy …”
Section: Introductionsupporting
confidence: 90%
“…Indeed, the above‐mentioned studies examined the expression of Cx43 in the frontal cortex whereas we recently found that prolonged administration of fluoxetine reduced the expression of phosphorylated Cx43 in the hippocampus . It is also noteworthy, that a recent work established that tricyclics, SSRIs and Serotonin Norepinephrine Reuptake Inhibitors antidepressant drugs unambiguously reduce the activity of hemichannels . This would suggest that the beneficial effects of Cx43 inactivation reported herein rely on its ability to block the hemichannels rather than gap junctions.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…In this study, we postulate that Cx-based astroglial networks might modulate DPZ pharmacological effects, and use validated mouse models for assessing our hypothesis. Mefloquine (MEF) was selected as a pharmacological tool to modulate astroglial Cxs, as previously reported both in vitro and in vivo (Picoli et al, 2012(Picoli et al, , 2019Jeanson et al, 2016;Droguerre et al, 2019).…”
Section: Introductionmentioning
confidence: 99%